Multiple thiol-anchor capped DNA–gold nanoparticle conjugates - Li, Zhi (Oxford University Press, 2002)
We report the synthesis of a novel trithiol-capped oligodeoxyribonucleotide and gold nanoparticle conjugates prepared from it. These DNA–gold nanoparticle conjugates exhibit substantially higher stability than analogs prepared from monothiol and cyclic disulfide-capped oligodeoxyribonucleotides, but comparable hybridization properties. A quantitative analysis of their stability under a range of conditions is provided. Significantly, this novel trithiol oligodeoxyribonucleotide can be used to stabilize particles >30 nm in diameter, which are essential for many diagnostic applications.